Power Aware Simulation Framework for Wireless Sensor Networks and Nodes. (2nd June 2008) - Glaser, Johann; Weber, Daniel; Madani, Sajjad A.; Mahlknecht, Stefan
Abstract : The constrained resources of sensor nodes limit analytical techniques and cost-time factors limit test beds to study wireless sensor networks (WSNs). Consequently, simulation becomes an essential tool to evaluate such systems.We present the power aware wireless sensors (PAWiS) simulation framework that supports design and simulation of wireless sensor networks and nodes. The framework emphasizes power consumption capturing and hence the identification of inefficiencies in various hardware and software modules of the systems. These modules include all layers of the communication system, the targeted class of application itself, the power supply and energy management, the central processing unit (CPU), and the sensor-actuator interface. The modular design makes it possible to simulate heterogeneous systems. PAWiS is an OMNeT++ based discrete event simulator written in C++. It captures the node internals (modules) as well as the node surroundings (network, environment) and provides specific features critical to WSNs like capturing power consumption at various levels of granularity, support for mobility, and environmental dynamics as well as the simulation of timing effects. A module library with standardized interfaces and a power analysis tool have been developed to support the design and analysis of simulation models. The performance of the PAWiS simulator is comparable with other simulation environments.